Development of Athletic Learning Model Based on Traditional Games in Class IV Students Primary School (SD) - Hari Dirjo Joko Susanto; Selvi Atesya Kesumawati; Bayu Hardiyono; Noviria Sukmawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Athletics is a sport that grows and develops along with natural human activities, running, jumping and throwing are an inseparable part of the long history of Indonesian life. The purpose of this study was to determine the results of the development of a traditional game-based athletic learning model for fourth grade elementary school students. The sample of the small group in this study were students of SD Negeri 87 Palembang, totaling 27 people, while the large group sample was SD Negeri 88 Palembang and SD Negeri 89 Palembang, amounting to 65 people. The stages of the development model carried out are the stages of model analysis, design, development, implementation and evaluation (ADDIE). The instrument used in this research is a questionnaire. The results of the expert validity test using the Content Validity Index (CVI) and Content Validity Ratio (CVR) in the Engklek Question game with an average CVR value of -0.225. Based on these results, it can be said that the development of a traditional game-based athletic learning model for fourth grade elementary school students has good quality as a learning resource.